Volcano Facies in Labanu Region, Tibawa District, Gorontalo Regency - Antoni, Isan; Permana, Aang Panji; Akase, Noviar (UNM Geographic Journal, 2025)
Located in Labanu Village, Tibawa District, Gorontalo Regency. The rocks contained in the study area are rocks originating from the Bilungala Volcano rock formation. This study aims to identify lithofasies of volcanic rocks based on differences in composition, structure, and texture. The method used is Measured Section (MS), in reducing the cross-section of measured stratigraphy, petrographic and petrological analysis carried out to divide the lithofasies of volcanic rocks. Lithofasies in the study area are divided into two lithofasies, namely: Lava lithofasies and pyroclastic lithopasies. In andesite facies lava lithofasies characterized by greenish-gray color, porphyritic texture, massive structure, degree of crystallization in andesite rocks is holocrystalline Most are composed of crystals, porphyritic texture, inequigranular crystal forms in these rocks are anhedral to subhedral, mineral compositions found megascopically include: plagioclase, pyroxene, hormblend, and a little pyroxene epidote and hormblend present as phenocryst,  and there is a small amount of secondary minerals in the form of epido. In pyroclastic lithofasies, lapilli facies has a characteristic light brown color, grain size (2 mm to 64 mm), the shape of the grain on this patuan is rounded and angled, it is interpreted that the deposition of this rock is some distance from the sembernya based on the size of the rock grain with the mass of the glass volcanic base, silica nin carbonate cement, poor sortation, open packaging, and has been compacted. Volcanic breccia facies have characteristics, among others: the color of light ash, the grain in this rock is gravel to kerakal (block), with angled grain bektuk responsibility until it is round (polymic), can be interpreted that this rock is far enough from the source based on the shape of the grain of the rock, pack it on this rock open container, poor sortation, igneous rock fragments in the form of andesite, non-carbonate silica cement, and glas volcanic matrix. While tuff facies has characteristics, brown color, grain size in this rock is fine, semaen in this rock is carbonate cement, closed packaging, has good sorting, weathered oxide (which is characterized by orange color), this rock has been compacted.